Ontogeny of Fetal Cardiometabolic Pathways: The Potential Role of Cortisol and Thyroid Hormones in Driving the Transition from Preterm to Near-Term Heart Development in Sheep - Reza Amanollahi; Stacey L. Holman; Melanie R. Bertossa; Ashley S. Meakin; Kent L. Thornburg; I. Caroline McMillen; Michael D. Wiese; Mitchell C. Lock; Janna L. Morrison (Journal of Cardiovascular Development and Disease)
Understanding hormonal and molecular changes during the transition from preterm to near-term gestation is essential for investigating how pregnancy complications impact fetal heart development and contribute to long-term cardiovascular risks for offspring. This study examines these cardiac changes in fetal sheep, focusing on the changes between 116 days (preterm) and 140 days (near term) of gestation (dG, term = 150) using Western blotting, LC-MS/MS, and histological techniques. We observed a strong correlation between cortisol and T3 (Triiodothyronine) in heart tissue in near-term fetuses, highlighting the role of glucocorticoid signalling in fetal heart maturation. Protein expression patterns in the heart revealed a decrease in multiple glucocorticoid receptor isoforms (GRα-A, GR-P, GR-A, GRα-D2, and GRα-D3), alongside a decrease in IGF-1R (a marker of cardiac proliferative capacity) and p-FOXO1(Thr24) but an increase in PCNA (a marker of DNA replication), indicating a shift towards cardiomyocyte maturation from preterm to near term. The increased expression of proteins regulating mitochondrial biogenesis and OXPHOS complex 4 reflects the known transition from glycolysis to oxidative phosphorylation, essential for meeting the energy demands of the postnatal heart. We also found altered glucose transporter expression, with increased pIRS-1(ser789) and GLUT-4 but decreased GLUT-1 expression, suggesting improved insulin responsiveness as the heart approaches term. Notably, the reduced protein abundance of SIRT-1 and SERCA2, along with increased phosphorylation of cardiac Troponin I(Ser23/24), indicates adaptations for more energy-efficient contraction in the near-term heart. In conclusion, these findings show the complex interplay of hormonal, metabolic, and growth changes that regulate fetal heart development, providing new insights into heart development that are crucial for understanding pathological conditions at birth and throughout life.